EVALUASI USER INTERFACE PADA SISTEM INFORMASI AKADEMIK DI STIE PUTRA BANGSA MENGGUNAKAN METODE USER CENTERED SYSTEMS DESIGN - Huda, Miftahul .; Winarno, Wing Wahyu; Lutfi, Emha Taufiq (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
This study aimed to evaluate the user interface of academic information system on ease of use (usability), provide recommendations based on the evaluation to enhance academic information systems and produce prototype user interfaceto enhance user acceptance levels of the academic information systems.The object of this study is academic information systems. This study uses a user centered design systems with some aspectsof the variables in the form of Visual Clarity, Consistency, Informative Feedback, Explicitness, Appropriate functionality,Flexibility and control. The sampling technique in this study using simple random sampling technique with a numberresponeden 30.Results from this study shown that the overall academic information system otherwise well. While the results show thatthe respondent's response assessment of academic information system on flexibility and control aspects of assessing4.44% for an answer "strongly disagree", 27.78% for an answer "do not agree", it shows that there are still many usersof information systems academic difficulty in using it.